The potential role of angiogenesis in the development of shoulder pain, shoulder dysfunction, and lymphedema after breast cancer treatment - Mafu, Trevor S (Cancer Manag Res, 2018)
Shoulder morbidity is a well-documented sequela of breast cancer treatment, which includes various manifestations such as pain, reduced range of motion, and lymphedema, among others. The multifactorial nature of such morbidities has long been appreciated, and research on reliable risk predictors of development thereof still continues. Previous studies have demonstrated the potential of different types of physical therapy to treat such shoulder problems, and the integration of such interventions into routine care for breast cancer survivors is a requirement in most high-income countries. Although patients at risk for developing shoulder problems would most likely benefit from posttreatment physical therapy, currently, there is no gold standard for identifying this patient group. This is particularly important in low- and middle-income countries where scarce monetary resources need to be directed specifically to those most in need. Modulators of the angiogenesis pathway have been implicated in noncancer shoulder conditions such as rotator cuff disease, adhesive capsulitis, and tendon injuries. The present review summarizes the role of angiogenesis in the development of shoulder morbidity among breast cancer survivors and sets forth the rationale for our belief that angiogenesis signaling may help explain a proportion of the reported clinical variability noted in the development of shoulder pain and dysfunction and upper-limb lymphedema after breast cancer treatment.